Non-leaky population transfer in a transmon artificial atom. (18th December 2017) - Yan, Run-Ying; Li, M; Zhao, Z Y; Lu, Xiao-Jing; Feng, Zhi-Bo
Abstract: We propose a theoretical scheme to implement non-leaky population transfer in a transmon-regime artificial atom. Due to the weak level anharmonicity of the transmon system, resonant driving leads to considerable quantum leakage. Facilitated by the level-transition rule, we develop a Λ-type interaction between the first three levels and the driving fields. Under two-photon resonance with large detuning, a reduced two-level system is obtained, with which we perform non-leaky population transfer by adjusting the microwave driving. With the accessible parameters, we further analyse the flexible reversibility and high robustness of the protocol. The present scheme provides a potential approach to optimizing population transfer with transmon artificial atoms.